Production of carbon-containing particles
The method of dispersing carbonizable precursors in a gas and heating them in a pulsed flow reaction region efficiently produces uniformly constructed anode particles with high discharge capacity, addressing the inefficiencies of current anode material production methods.
Patent Information
- Application Number
- JP2022557946
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-26
- Filing Date
- 2021-03-24
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Current methods for producing anode materials for batteries are inefficient and not scalable for mass production, leading to challenges in meeting the increasing demand for battery capacity.
A method involving the dispersion of a carbonizable precursor and/or carbon-containing raw material in a gas, which is then sent to a reaction region where it is heated to form carbon-containing particulate products. The gas flows in a pulsed manner to maintain turbulence and facilitate efficient carbonization.
This method enables the continuous production of uniformly constructed anode particles with a specific discharge capacity of 100 mAh/g or greater, making it suitable for high-performance battery anodes and scalable for mass production.
Smart Images

Figure 0007657823000001 
Figure 0007657823000002 
Figure 0007657823000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a carbon-containing granular product, a carbon-containing granular product, and its use for producing anodes in batteries. [Background technology]
[0002] It is known that certain particles can be formed or modified in a targeted manner in a gas stream, where the material is gas-entrained, i.e. dispersed in a carrier gas.
[0003] US Patent No. 5,399,663 describes the synthesis of carbon granules in a nitrogen gas stream in a fluidized bed reactor. In this document, granules of microcrystalline cellulose dried at 100° C. are used. As the temperature is increased over time from 200° C. to 433° C., the mass of the granules decreases from 15.1 g to 3.9 g. The carbon granules of US Patent No. 5,399,663 are said to function as a support structure for solid catalysts.
[0004] For example, in the powder thermal synthesis process described in [1], a pulsed gas flow is generated, the gas flow is temperature controlled to generate droplets from an atomized liquid, the powder is synthesized, dried and heat-treated, and finally cooling air is used to abruptly stop the synthesis or to stop the heat treatment. A filter is used to separate the powder from the gas flow. The process is described as being suitable for a wide variety of raw materials. Spray sintering is ideal for the production of ceramic oxides, nitrides and sulfides, as well as other product groups such as metal oxides. It offers advantages in the production of mixed oxides of the spinel, perovskite and titanate types. The production of cell components and cathode materials for fuel cells is also described.
[0005] Patent document 2 also describes a method and a reactor for producing certain particles. The method comprises the steps of introducing at least one raw material into a reactor, heat treating the at least one raw material with a pulsed process gas flow in a processing area of the reactor, forming particles, and discharging the resulting particles from the reactor. In the method, the temperature control of the process gas flow is separated from the generation and management of the pulsation of the process gas flow. Indirect heating offers the advantage of making the method suitable for pharmaceutical and food industry production processes.
[0006] US Patent No. 5,399,633 relates to a method for producing expanded graphite, in which the intercalated graphite is thermally shocked by pulsed combustion in a pulse reactor. The pulse reactor in this document includes a combustion chamber. A fuel-air mixture enters the combustion chamber and is ignited, causing rapid combustion. Upon entering the combustion chamber, the intercalated graphite is introduced in the form of a dispersion, preferably using a nozzle, which finely disperses the intercalated graphite into the combustion chamber or into a downstream resonator tube, where rapid dehydration or pyrolysis of the dispersion medium takes place. This document also relates to the use of the resulting expanded graphite as a conductive component in batteries and fuel cells. It is not specified where in the battery the conductive properties of the expanded graphite are to be used.
[0007] Patent Document 4 describes a method for producing an electrode material for lithium-sulfur batteries using an electrode active material containing a polyacrylonitrile-sulfur composite. Particles of the polyacrylonitrile-sulfur composite are at least partially coated with a carbon-modified coating. In the method, a composite formed of sulfur and polyacrylonitrile is coated with a carbon-modified coating by adding a carbon-releasing compound. In this case, a suspension of a pre-prepared sulfur-acrylonitrile composite is spray-pyrolyzed together with a carbonizing agent (e.g. a solution of citric acid or glucose) at a temperature preferably below 200°C.
[0008] For the production of anode materials for lithium-ion batteries, attempts have been made to targetably coat particles in gas or to carbonize the particles in gas during specific process steps.
[0009] Non-Patent Document 2 describes the coating of silicon nanoparticles with polyvinyl alcohol (PVA) by spray drying. Prior to carbonization, the silicon particles are specially treated in air at 200 °C for 16 h to crosslink the PVA. Carbonization is carried out in nitrogen at 1050 °C. The resulting Si / C composite is suitable as an anode material for Li-ion batteries.
[0010] A similar method is described in Non-Patent Document 3. Silicon nanoparticles are coated with PVA by spray drying, and then the PVA-coated silicon nanoparticles are coated with polyacrylonitrile (PAN). The PVA- and PAN-coated silicon nanoparticles are then stabilized at 250°C in contact with air, and carbonized at 800°C in contact with argon.
[0011] In addition, in the method for producing pre-composite particles described in Patent Document 5, a mixture of silicon particles, one or more oxygen-free polymers, one or more carbon additives based on carbon modification, and one or more dispersions is dried by spray drying. Heat treatment of the pre-composite particles obtained by spray drying is also described. This is carried out at 400°C to 1400°C in a tube furnace, a rotary tube furnace, or a fluidized bed reactor. For example, the first heat treatment is carried out in an oxygen-containing atmosphere at a temperature of 300°C or less, and the second heat treatment is carried out in an inert gas atmosphere at a temperature of more than 300°C.
[0012] In the method described in US Pat. No. 6,593,516, a polyimide layer is first synthesized on the surface of silicon nanoparticles from a diamine and a carboxylic anhydride. The solvent used to form the polyimide layer (e.g., N,N'-dimethylacetamide) is removed by spray drying. The spray-dried material is then heated to 600°C at 3°C / min and kept at that temperature for 1 hour. Additional process steps, such as grinding without damaging the coating and mixing with graphite powder, are necessary before the product can be used as an anode.
[0013] In US Pat. No. 5,399,414 it is proposed to dissolve citric acid in absolute ethanol, add silicon powder that has been pretreated in a specific manner with NaOH to the solution, stir with ultrasonic treatment, and react the resulting mixture by spray pyrolysis at 400° C. in air to form a silicon carbon composite.
[0014] The method described in this document for the production of anode materials, which leads to the desired C-Si composite anode materials through subsequent process steps, is not feasible or requires a great deal of effort for mass production.
[0015] The dramatic expansion of electromobility requires particularly efficient methods for producing high performance anode materials capable of meeting the increasing battery capacity demands for extended periods of time. [Prior art documents] [Patent documents]
[0016] [Patent Document 1] DE 102006022866 [Patent Document 2] DE 102018205152 [Patent Document 3] German Patent No. 10328342 [Patent Document 4] DE 102015219473 [Patent Document 5] International Publication No. 2017 / 148871 [Patent Document 6] China Patent Application Publication No. 106207142 [Patent Document 7] China Patent Publication No. 106129371 [Patent Document 8] European Patent Application Publication No. 3746215 [Non-patent literature]
[0017] [Non-Patent Document 1] cfi / Ber. DKG 96 (2019) No. 11-12, pages D9-D12 [Non-Patent Document 2] Paireau et al., Electrochimica Acta, 2015, 174, pages 361-368 [Non-Patent Document 3] Li et al., Electrochemistry Communications, 2014, 49, pages 98-102 [Non-Patent Document 4] Compendium of Chemical Terminology, 2nd ed. (the "Gold Book"), Compiled by AD McNaught and A. Wilkinson, Blackwell Scientific Publications, Oxford (1997), Online version (2019-) created by SJ Chalk, ISBN 0-9678550-9-8, https: / / doi.org / 10.1351 / goldbook Summary of the Invention [Problem to be solved by the invention]
[0018] It is an object of the present invention to provide a particularly efficient method for the continuous production of uniformly structured anode material particles. [Means for solving the problem]
[0019] This object is achieved by a method for producing a carbon-containing particulate product, comprising dispersing a carbonizable precursor and / or a carbon-containing raw material in a gas and feeding it to a reaction zone to form at least a portion of the carbon contained in the product, and pulsing the gas at least in the reaction zone.
[0020] The actual meaning of pulsing is described in US Pat. No. 5,999,663. Carbon-containing can mean comprising any form of carbon material, in particular non-graphitic carbon-based materials, amorphous carbon-based materials, graphitic carbon-based materials, and / or graphite (unexpanded or expanded forms of graphite). The materials described here are as defined by IUPAC. See US Pat. No. 5,999,663. For non-graphitic carbon-based materials, see the entry "non-graphitic carbon" in this document. Similarly, for amorphous carbon-based materials, see "amorphous carbon", for graphitic carbon-based materials, see "graphitic carbon", and for graphite, see "graphite".
[0021] According to the present invention, the raw material contains a carbonizable precursor and / or carbon. The carbon that may be contained in the raw material is as described above for the carbon contained in the product. Thus, the carbon-containing raw material may contain the same carbonaceous materials as those described above.
[0022] The carbon contained in the raw material may preferably be selected from coke particles, carbon black particles, graphite particles, expanded graphite particles, graphene, milled carbon fibers, carbon nanotubes, or vapor-grown carbon fibers, which means that the carbonization may be partial, since part of the material converted into the product is already carbonized.
[0023] The carbonizable precursor described herein is a precursor having a material yield of 10% by weight or more, in particular 20% by weight or more, when heated in N2 atmosphere. This is checked by weighing approximately 1 milliliter of precursor, heating it in N2 atmosphere at a heating rate of 1 K / min to 900° C. and holding it at 900° C. for another 10 minutes in N2 atmosphere. The residue is weighed again. If the mass of the second weighing is 10% by weight or more of the mass of the first weighing, the material yield is 10% by weight or more. The mass fraction of carbon in the residue can be 80% by weight or more, for example 90% by weight or more. The carbonizable precursor can be preferably selected from pitch (e.g. coal tar pitch, petroleum pitch), bitumen, heavy oil, resin (e.g. phenolic resin, furan resin, epoxy resin, cyanate ester resin), polyacrylonitrile, polyimide, carbohydrate (e.g. sugars), lignin, polyethylene, polystyrene, polyvinyl chloride, or mixtures thereof. Furthermore, the polymers may comprise copolymers, which leads to particularly efficient products, since particularly preferred educts are used and react rapidly in large quantities using the particularly simple method according to the invention.
[0024] According to the invention, the raw material is dispersed in the gas. This can be done via a suitable inlet. The inlets described in US Pat. No. 5,999,333 are suitable, in particular nozzles, for example spray nozzles. The raw material is conveyed through the nozzle and in the process is separated into a number of small droplets which are dispersed in the gas. Depending on the melting point and viscosity of the raw material, the skilled person will appropriately adjust the temperature of the raw material so that it can be completely dispersed in the gas stream by means of the nozzle.
[0025] The raw materials dispersed in the gas are fed to the reaction zone. There are two fundamentally different ways of feeding the dispersed materials into the reaction zone. The gas and the materials dispersed therein can be fed in countercurrent to each other. The reaction zone is then preferably oriented vertically and the materials dispersed in the gas sink below the reaction zone against the gas flow direction. A particle outlet is then preferably located below the reaction zone. At the particle outlet the particles produced are removed from the system via a lock system. The gas and the materials dispersed therein can also be fed in parallel to each other. The effect of this is that the gas and the materials dispersed therein can be fed together into the system but can be passed through different temperature and turbulence zones in a targeted manner.
[0026] According to the invention, at least part of the carbon-containing product is formed in the reaction zone. For this purpose, the temperature of the material dispersed in the gas in the reaction zone is raised to a temperature at which carbon is formed. In this case, the carbonizable precursor contained in the raw material can serve as a source for forming carbon. At least part of the carbonizable precursor is then carbonized in the reaction zone, from which at least part of the carbon contained in the product is formed. At least part of the carbon comes directly from the carbonizable precursor without the need to add an additional carbon source to the process. This is preferred because a liquefied carbonizable precursor can be easily used. The liquefied precursor can also serve as a carrier liquid in which the solid components contained in the raw material (e.g. carbon or the submicron material (or its precursor) described below) can be dispersed. Such a dispersion can be continuously pumped through an inlet, allowing a particularly efficient process control. If necessary, an organic solvent (e.g. xylene) capable of partially or completely dissolving the particular carbonizable precursor can be added to fully liquefy the precursor. It is therefore preferred that the raw material is at least partially liquid. This is advantageous because the raw material can be dispersed as fine droplets in a laminar or turbulent flow of gas using nozzles (one-material nozzles, two-material nozzles, three-material nozzles, ultrasonic nozzles, centrifugal atomizers, etc.). However, other carbonizable materials fed to the reaction zone can also serve as a source of carbon to be formed, including, for example, hydrocarbons, which can form reactive components of the feed gas, as described below.
[0027] The gas flows in pulses through the reaction region so that turbulent flow is maintained in at least a portion of the reaction region.
[0028] Depending on the composition of the mixture of gases and (raw) materials present in the reaction zone and dispersed therein, the temperature required to form at least a portion of the carbon contained in the product in the reaction zone may vary. It is known that certain carbonizable precursors (e.g., carbohydrates) react at very low temperatures to form carbon residues, while more extreme conditions are required to carbonize thermally stable carbonizable precursors.
[0029] Typically the material dispersed in the gas is heated in the reaction zone to a temperature of at least 200°C, preferably at least 400°C, more preferably at least 600°C, for example at least 800°C.
[0030] The carbon-containing granular product obtained by the exemplary process control according to the present invention is suitable for use as an anode material in batteries. Accordingly, the present invention relates to a method for producing a carbon-containing granular product for use as an anode in batteries.
[0031] Typically the carbon-containing granular product has a specific discharge capacity of 100 mAh / g or greater for a charge carrier selected from Li, Na, Al, Mg, Zn, preferably Li.
[0032] The discharge capacity is determined by preparing electrodes and analyzing them in laboratory half cells (2016 type button cells) using a Maccor 4000 battery tester. For the preparation of the electrodes, 80 parts by weight of the carbon-containing granular product are mixed with 8 parts by weight of CMC (carboxymethyl cellulose) binder (approximately 700000 g / mol, commercially available from Acros), 12 parts by weight of conductive carbon black Super P (commercially available from Imerys), and deionized water to form an ink. The amount of water is selected as necessary to adjust the viscosity of the ink in question. The ink is coated onto a copper foil (rough, 20 μm thick, commercially available from Schlenk) using a table-top film applicator with a blade gap height defined to give the desired loading per unit area. The coating is dried in a controlled manner and a circular electrode plate (14 mm diameter) suitable for a 2016 type button cell is die-cut (all equipment and housing parts for constructing the button cell are commercially available from Hohsen). The electrode mass on the copper foil is determined by weighing, so the mass of copper is subtracted from the mass of the electrode plate. The electrode plate is dried (in vacuum, >110°C) and placed in an argon-filled glove box together with a die-cut lithium foil (16 mm diameter, commercially available from Alfa Aeser) as a counter electrode, a separator (GF / D, commercially available from Whatmann), and an electrolyte to form a coin cell (half cell). The electrolyte (premixed from Ube Industries) had the following composition: 1 mol / L lithium hexafluorophosphate + 2% vinylene carbonate + 10% fluoroethylene carbonate dispersed in ethylene carbonate / ethyl methyl carbonate (volume ratio 1:1).
[0033] The battery is charged and discharged ("cycled") in a battery tester (Maccor series 4000) with the lithium counter electrode of the half-cell structure also used as potential reference. The battery test is carried out under the following conditions: formation (3 cycles) charge 0.1C CC at 20mV, CV at C / 100; discharge 0.1C CC at 1.5V. (After formation) cycle charge 0.5C CC at 20mV, CV at C / 20; discharge 0.5C CC at 1.5V (CC=constant current, CV=constant voltage). The specific discharge capacity is for the first formation cycle. When calculating the specific discharge capacity, only the mass of the granular product according to the invention is taken into account, i.e. only 80% of the electrode mass on the copper foil is taken into account, which is weighed and subtracted.
[0034] It is preferred to feed the gas and the materials dispersed therein, for example in a pulsed manner, so that at least a part of the raw materials, particularly preferably all of the raw materials, remain continuously dispersed in the gas and react in the gas, at least until the carbon-containing particulate product is formed. The advantage is that the production can be carried out at a particularly high speed with minimal expenditure on the equipment. Only the fluid (or a dispersion behaving like a fluid) needs to be fed, and no solids or the like need to be handled. When the gas flows in pulses, it promotes the formation of turbulence, so that it is simple to keep some or all of the raw materials continuously dispersed in the gas and react in the gas, at least until the carbon-containing particulate product is formed. If necessary, the frequency and / or amplitude of the pulsed gas flow can be optimized.
[0035] The raw material preferably includes submicron material (e.g., submicron particles) and / or submicron material precursor (e.g., submicron particle precursor). Alternatively, the submicron material precursor (e.g., submicron particle precursor) and / or the submicron material (e.g., submicron particles) may be directly dispersed in the gas. These two preferred exemplary methods allow for the in situ formation of submicron material carbon composite particles, particularly submicron particle carbon composite particles.
[0036] Silanes (e.g., SiH4, Si2H6), halogen-containing silanes (e.g., SiH3Cl, SiH2Cl2, SiHCl3, SiCl4, mixtures thereof), alkylsilanes, alkoxysilanes, and equivalent tin compounds (stannanes) can be used as submicron material precursors (e.g., submicron particle precursors). When certain volatile or gaseous precursors are directly dispersed in a gas, they form a homogeneous mixture with the gas, i.e., they are molecularly dispersed in the gas.
[0037] If the raw material contains submicron material or its precursor, the fluid only needs to be added to the gas, which is particularly simple in a mixing chamber with two inlets. The submicron material contained in the raw material tends to be embedded in the particle matrix of the submicron material carbon composite particles and does not concentrate on the particle surface. Thus, submicron material carbon composite particles are obtained by these two preferred method examples, and the submicron material can be present in the form of particles, fibers and / or layers inside and / or outside the carbon as desired, for example, in the pores (open pores, closed localized pores), embedded in the C matrix (dense, globally porous matrix) or present on the carbon surface.
[0038] It should be understood that in these two preferred method examples, submicron material precursors (e.g. submicron particle precursors) are converted into submicron materials (submicron particles). The submicron particles are formed in situ without the need for additional processing. This approach is therefore very efficient. It also results in composites with submicron or nanomaterials, with properties that cannot be obtained by adding the submicron materials separately. In this case, the particles or nanoparticles (e.g. copper, copper oxide, nickel, etc.) present in the raw material act as catalysts and / or crystallization nuclei in the conversion of the submicron material precursors into the submicron materials, resulting in targeted localized deposition of the submicron materials in the process.
[0039] Here, submicron material means material having an average size of less than 1 μm. Submicron particles means particles having an average diameter of less than 1 μm, as measured by SEM (scanning electron microscope) for particles obtained by the method according to the invention.
[0040] Here, submicron material means a material having an average size preferably less than 800 nm, particularly preferably less than 500 nm, most preferably less than 200 nm. Submicron particles means particles having an average diameter preferably less than 800 nm, particularly preferably less than 500 nm, most preferably less than 200 nm. Submicron material means a material having an average size preferably greater than 10 nm, more preferably greater than 20 nm, most preferably greater than 30 nm. Submicron particles means particles having an average diameter preferably greater than 10 nm, more preferably greater than 20 nm, most preferably greater than 30 nm. At even smaller sizes, the structures and particles become too reactive and may be difficult to handle. They also have a relatively thick surface layer. Size and diameter are measured by SEM.
[0041] The submicron material preferably comprises a storage material for charge carriers selected from Li, Na, Al, Mg, Zn. This has the effect of increasing the ion storage capacity compared to pure carbon materials. The storage material is particularly preferably a storage material for lithium, for example selected from silicon and tin. Typically, when submicron silicon precursors (e.g. submicron silicon particle precursors) or submicron silicon (e.g. submicron silicon particles) are fed to the reaction zone, the gas dispersion in the reaction zone is heated to a temperature of up to 1600° C. It has been found that the undesirable reaction of silicon with carbon to form silicon carbide is largely prevented by keeping the treatment time short.
[0042] The gas in which the raw material is dispersed preferably contains an inert gas component (e.g., He, Ar, N2), which may be present in an amount of 30% by volume or more, for example 50% by volume or more. The effect of this is that adverse side reactions such as carbon combustion are suppressed, so that the carbonizable precursor can be pyrolyzed to form carbon with a high yield. The proportion of oxygen molecules (O2) in the gas in which the raw material is dispersed is generally 8% by volume or less, in particular 5% by volume or less, preferably 2% by volume or less, for example 0.5% by volume or less.
[0043] It is also preferred that the gas in which the feedstock is dispersed contains reactive components, particularly halogens and halogen-containing compounds that are vaporizable under process conditions, hydrocarbons (e.g., methane, acetylene, benzene, toluene, xylene), H2, CO, CO2, NH3, H2O, and ozone. By precisely adjusting the gas composition and the temperature of the reaction zone, secondary chemical reactions can be targeted and controlled, such as: - Carbon Deposition - Silicon Deposition - Activation (increase in pore volume and surface area) - Reduction - Oxidative crosslinking - Oxidative cleaning of carbon from metal impurities (ash)
[0044] Within the reaction zone, the mass fraction of the reactive gas in the gas is typically reduced, the effect of which is that the achievement of at least one side reaction can be assessed by observing at least one reactive component in the gas stream.
[0045] Preferably, at least a portion of the gas is recycled to flow at least multiple times through the reaction zone, the advantage of which is that the process becomes more economical since the inert gas is a cost factor and complex purification of the non-recycled portion of the gas stream can be omitted.
[0046] The pulsating gas flow, at least in the reaction zone, creates turbulence in the reaction zone. U.S. Patent No. 5,399,433 provides a detailed description of maintaining the pulsating flow in the reaction zone even in the absence of combustion waste gas flowing through the reaction zone. Reference is made to U.S. Patent No. 5,399,433 for the technical implementation of the pulsating flow in the context of the present invention.
[0047] The method according to the invention is preferably carried out in such a way that the gas is pulsed at a frequency of ≧1 Hz and ≦50000 Hz, for example ≦5000 Hz.
[0048] The ability to provide targeted and controlled turbulence within the reaction zone provides many advantages, as will be described below.
[0049] The (raw) material dispersed in the gas can be rapidly heated, for example within 0.1 seconds, to 10 K or more, in particular 20 K or more, preferably 40 K or more, particularly preferably 70 K or more. Rapid heating also ensures a very uniform material and temperature distribution. This ultimately results in a granular product in which each particle has undergone approximately the same conditions (reaction conditions, temperature conditions), and thus in a particularly uniformly structured granular product. This is important for electrode materials (e.g. anode materials), in particular for submicron material carbon composite particles, where the submicron material comprises silicon or tin and can intercalate large amounts of lithium. In this case, particularly uniform production conditions are crucial for the reliability of the battery.
[0050] A particular feature of the method according to the invention is that it is possible to effect gas-liquid-solid reactions in a targeted manner. For example: - Conversion of solid to gas (pitch → pyrolysis gas) - liquid to gas conversion (toluene → evaporation) and / or - Conversion of any gas (e.g. product gas) to solid (pyrolysis gas / gaseous toluene → carbon) For example, targeted release of reactive gases from solid carbonizable precursors and / or carbon, which allows for in situ coating of dispersed materials with carbon.
[0051] A further special feature of the method according to the invention is that the unusually rapid heating, compared to comparable decomposition reactions, can promote the sublimation of difficult to sublimate solids and the evaporation of semi-volatile liquids. A portion of the resulting gas can contribute to the formation of a carbon layer on materials dispersed in the gas.
[0052] It is not necessary to feed the material dispersed in the gas directly to the reaction zone. The invention also includes a method in which the raw material is first fed to a pretreatment zone. In this case, the raw material is converted into the pretreatment material, for example by polymerization, crosslinking, and / or pore formation. The pretreatment material can then be fed to the reaction zone. This allows the structure and morphology of the particles to be partially defined before carbonization. Polymerization and / or crosslinking in the pretreatment zone can be performed by irradiation, temperature increase, and / or feeding initiators and catalysts for the polymerization and crosslinking reactions. The pores can be formed by increasing the temperature of the pretreatment zone to a temperature at which volatile components of the raw material become gaseous and at least partially escape from the remaining raw material through the pores of the resultant product. The volatile components can also result, for example, from the decomposition of ammonia compounds or other gas-forming chemical reactions. The effect of this is that the pores in the remaining raw material become accessible to the reactive components of the gas. The extent of pretreatment achieved (for example, the extent of pore formation, the extent of polymerization, the extent of crosslinking) can be determined directly or indirectly. The process parameters critical to the extent of pretreatment can be adjusted if pretreatment is not achieved to the desired extent. The raw material may comprise 0.1% by weight or more of volatile components that will boil or decompose at the pressure and temperature conditions prevailing in the pretreatment zone. The effect of this is that pores are formed in the carbon material and further reactive components may be formed that decompose at high temperatures to form carbon.
[0053] The particles obtained from the reaction zone may be further processed. Further processing according to the invention may include separating the particles (e.g. using sieves), mixing the particles with other particles (e.g. graphite particles) and / or mixing the particles with a binder to form an anode material paste. In one development of the method according to the invention, the anode material paste may be applied to an electrical conductor to produce an anode for a battery.
[0054] The process according to the invention makes it possible to obtain specific carbon-containing granular products, which are a further subject of the invention.
[0055] The present invention therefore also relates to carbon-containing granular products, in particular anode materials for batteries (e.g. submicron material-carbon composite particles, where the submicron material comprises silicon or tin), The product has matrix regions that are at least partially inaccessible to xylene when determining density by specific gravity; the product has a specific gravity determined density that is at least 10%, preferably at least 15%, in particular at least 20% or more, particularly preferably at least 25% lower than a ground sample of the same carbonized particulate material; The product has an average sphericity ψ in the range of 0.35-1, preferably in the range of 0.55-1, and most preferably in the range of 0.85-1.
[0056] A crushed sample of the same carbonized granular material is prepared by crushing the powder using a ball mill. The powder is placed in a crushing vessel already containing crushing balls (e.g., steel balls). The crushing vessel is then rotated using a suitable device (e.g., a rotating block). After crushing, the powder is removed from the crushing vessel and a xylene specific gravity measurement is performed. The crushing is performed to determine the average particle size (d 50 The particle size (d 50 ) is determined by laser diffraction methods.
[0057] The sphericity ψ is the ratio of the surface area of a sphere of the same volume to the surface area of the actual object (Wadell's definition). The sphericity can be determined, for example, from conventional SEM recordings.
[0058] Carbon-containing granular products, in particular battery anode materials (e.g. submicron material-carbon composite particles, where the submicron material comprises silicon or tin), can be obtained by the method according to the invention. In this case, the anode material particles can be provided such that their shape is to a good approximation approximately spherical. Thus, uniformly structured anode material particles are obtained.
[0059] The submicron material-carbon composite particles according to the present invention (wherein the submicron material comprises silicon or tin) are preferably submicron carbon composite particles, the submicron particles being selected from submicron silicon particles and submicron tin particles. Such granular products according to the present invention preferably satisfy the following conditions: d50 sub ·(x c / x sub )>s During the ceremony, d50 sub is the average submicron particle size in pm, x c is the mass fraction of carbon in the total mass of the granular product, x sub is the mass fraction of submicron particles in the total mass of the granular product, s is a safety parameter which is 0.02, in particular 0.03, preferably 0.04, particularly preferably 0.05.
[0060] For example, d50 Si If there are small submicron silicon particles with a diameter of 0.01 μm (= 10 nm), the carbon fraction must be at least twice the silicon fraction to satisfy the above inequality. Si When the thickness is 0.03 μm (= 30 nm), the above inequality is satisfied if there is slightly more silicon than carbon.
[0061] If the ratio of carbon to silicon in the granular product is matched with the silicon particle size according to the above conditions, it is always sufficiently guaranteed that the silicon is covered with carbon or embedded in carbon, regardless of the silicon particle size. This condition specifically requires a high carbon mass fraction, especially when small silicon particles with a large specific surface area are used. However, a low carbon mass fraction can be used when large silicon particles with a small specific surface area are used. This ensures that the silicon surface area accessible to the electrolyte is as small as possible, regardless of the silicon particle size. A small silicon surface area accessible to the electrolyte is said to result in a more uniform and less SEI formation, and also a more uniform current density distribution to the anode, which ultimately makes the battery more reliable. The silicon covering or silicon embedding also inhibits the silicon particles from jumping out of the composite. The electrical contact between the individual silicon particles and the current collector remains reliable. Thanks to the continuous electrical contact, the particles remain active and well involved in the charge and discharge process of the battery. This reduces the capacity loss with repeated charging and discharging. The same applies in the case of tin particles.
[0062] The carbon-containing granular product, in particular the anode material of the battery (e.g. submicron material carbon composite particles, where the submicron material comprises silicon or tin), preferably comprises core-shell particles, for example core-shell composite particles. As mentioned above, the method according to the invention allows for the separation of carbon from the gas phase. This is used to advantage, in particular by incorporating a coating of the granular product directly during the process, which coating forms the shell of the core-shell composite particle.
[0063] A further subject of the invention relates to the use of a granular product according to the invention or obtained by the process according to the invention for the manufacture of anodes for batteries.
[0064] The invention is illustrated but not limited in the drawings in the following description. [Brief description of the drawings]
[0065] [Figure 1] 1 shows a diagram of a system for carrying out the method according to the invention; [Diagram 2] 1 shows a diagram of a system for carrying out the method according to the invention; [Diagram 3] 1 shows a diagram of a system for carrying out the method according to the invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0066] The method according to the invention for producing a carbon-containing granular product suitable for battery anode material can be carried out in a system as shown diagrammatically in Fig. 1 to Fig. 3. In this case, the raw material (for example a dispersion containing silicon submicron particles, pitch and xylene) is sprayed from a storage container 1 via a pump 2 and a nozzle (not shown) into a mixing chamber 3. The pitch is a carbonizing precursor. The amount of xylene is selected so that the raw material is at least partially liquid and sufficiently fluid to be pumped. The raw material may also contain carbon, for example dispersed graphite particles and / or soot particles. The raw material is dispersed in gas via a nozzle 5 and fed into the mixing chamber 3 via a pulsing unit 4. The gas fed through the gas inlet 5 may for example be mainly composed of nitrogen molecules and may contain reactive components, for example hydrocarbons and very small amounts of oxygen molecules. The raw material dispersed in gas is fed into a reaction zone 7 located in a reactor 6 equipped with a heating jacket. The material dispersed in the gas is heated in the reaction zone 7 to a temperature of 800 ° C to 1400 ° C, and the pitch is carbonized in the reaction zone 7, from which at least a part of the carbon contained in the product is formed. The pulsing unit 4 ensures that the gas flows in pulses at least in the reaction zone 7, for example pulsing at a frequency of 500 Hz. In the pulsing unit 4, a pressure gradient is maintained across the passages which alternately open and close at the desired frequency, so that whenever the gas flows through the open passage, a maximum of the pressure pulse occurs immediately after the passage in the direction of gas flow, and whenever the passage is closed, a minimum of the pressure pulse occurs immediately after the passage in the direction of gas flow. The pressure wave thus generated propagates through the reaction zone 7. The gas and the material dispersed therein are directed in such a way that the raw materials remain continuously dispersed in the gas and react in the gas to form the carbon-containing granular product. The gas discharged from the reaction zone 7 and the granular product dispersed therein are mixed in the cooling zone 9 with the cooling gas supplied via the cooling gas inlet 8 and directed to the particle separator 10. The granular product is obtained from the particle separator via a particle outlet 12. The gaseous components of the stream fed into the particle separator 10 pass through a gas outlet 11.
[0067] In the systems according to figures 2 and 3, the raw material dispersed in the gas first passes through a pre-treatment zone 13. The raw material dispersed in the gas is heated in the pre-treatment zone 3 to a temperature between 100°C and 300°C. In this case, small amounts of oxygen molecules can act as initiators of radical reactions, resulting in the desired cross-linking of the low volatility organic components of the raw material.
[0068] 3 shows that it is not necessary to send all of the supplied gas to the pulsing unit 4, nor is it necessary for the pulsing unit to be located upstream of the mixing chamber 3. In the example shown, of the two gas inlets 5A, 5B, one gas inlet 5A is connected directly to the mixing chamber 3 and the other gas inlet 5B is connected directly to the pulsing unit 4. [Explanation of symbols]
[0069] 1. Storage container 2. Pump 3 Mixing chamber 4 Pulsing unit 5, 5A, 5B Gas Inlets 6. Reactor 7. Reaction Area 8 Cooling Gas Inlet 9 Cooling area 10 Particle separator 11 Gas Outlet 12 Particle Outlet 13 Pre-processing area
Claims
1. 1. A method for producing a carbon-containing granular product comprising submicron material carbon composite particles, comprising dispersing a feedstock material containing a carbonizable precursor and a submicron material and / or a submicron material precursor in a gas and delivering it to a reaction zone in which at least a portion of the carbon contained in the carbon-containing granular product is formed, the gas flows in a pulsed manner at least in the reaction zone, and the feedstock material further comprises carbon.
2. 2. The method of claim 1, wherein the gas and the raw material dispersed in the gas are directed such that at least a portion of the raw material remains continuously dispersed in the gas and reacts in the gas until at least a portion of the raw material forms the carbon-containing particulate product.
3. The method of claim 1 , wherein at least a portion of the carbonizable precursor is carbonized in the reaction zone to form at least a portion of the carbon contained in the carbon-containing particulate product.
4. The method of claim 1 , wherein the submicron material precursor is a submicron particle precursor and / or the submicron material is a submicron particle.
5. The method of claim 1 , wherein the sub-micron material precursor reacts to form a sub-micron material.
6. 5. The method of claim 1 or 4, wherein the submicron material comprises a storage material for charge carriers selected from Li, Na, Al, Mg and Zn.
7. The method of claim 1 , wherein the feedstock is at least partially liquid.
8. 2. The method of claim 1, wherein the carbonizable precursor is selected from pitch, bitumen, heavy oil, resin, polyacrylonitrile, polyimide, carbohydrate, lignin, polyethylene, polystyrene, polyvinyl chloride, or mixtures thereof.
9. The method of claim 1 , wherein the gas through which the raw material is dispersed comprises an inert gas component.
10. The inert gas component is He, Ar, or N 2 The method according to claim 9, wherein
11. The method of claim 1 , wherein the gas and the feedstock dispersed therein are passed in co-current flow.
12. The method of claim 1 , wherein the gas and the raw material dispersed therein are conveyed in countercurrent flow.
13. 2. The method of claim 1, wherein the carbon contained in the raw material is selected from coke particles, carbon black particles, graphite particles, expanded graphite particles, graphene, milled carbon fibers, carbon nanotubes, vapor grown carbon fibers, or mixtures thereof.
14. 14. Use of a carbon-containing granular product produced by the method of any one of claims 1 to 13 for producing an anode of a battery.
Citation Information
Patent Citations
Silicon-carbon composite assembled battery
CN106129371A
Power lithium ion battery silicon-carbon composite negative electrode material preparation method
CN106207142A
carbon granulate, process for its production and its use
DE102006022866A1
Electrode material, battery cell containing this and method for their production
DE102015219473A1
Process and reactor for the production of particles
DE102018205152A1